2014
DOI: 10.1002/ep.11992
|View full text |Cite
|
Sign up to set email alerts
|

Production of bioethanol from rice straw by simultaneous saccharification and fermentation of whole pretreated slurry usingSaccharomyces cerevisiaeKF-7

Abstract: Rice straw is one of the most abundant lignocellulosic waste materials worldwide, and it can serve as feedstock for bioethanol production. In this study, ethanol was produced from rice straw by simultaneous saccharification and fermentation (SSF) of the whole pretreated slurry with high solid load. Pretreatment of rice straw using 0.5% (w/w) H2SO4 was performed to increase the efficiency of enzymatic saccharification. Enzymatic saccharification and SSF of the whole pretreated slurry were subsequently performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Wang et al . () have reported that fermentation using the thermotolerant S. cerevisiae KF‐7 at 35°C achieved a theoretical yield of 77.3%, which was comparable to our results; however, the solid loading (20% (w/v) is equal to 19.58% (w/w) derived from the density 1.12 g/cm 3 of pretreated solid residue in dry basis) that we used and the ethanol titre (33.4 g p l −1 ) with P. kudriavzevii SI were higher than those with S. cerevisiae KF‐7, that is a solid loading of 15% (w/w) and 21.5 g p l −1 ethanol respectively. Although the concentration of acetic acid presented in their SSF process was similar with that in our study, the concentration of furans presented in their results (furfural 0.8 g l −1 and 5‐HMF 0.2 g l −1 ) was higher than that in our process (furfural 0.19 g l −1 ).…”
Section: Resultssupporting
confidence: 87%
“…Wang et al . () have reported that fermentation using the thermotolerant S. cerevisiae KF‐7 at 35°C achieved a theoretical yield of 77.3%, which was comparable to our results; however, the solid loading (20% (w/v) is equal to 19.58% (w/w) derived from the density 1.12 g/cm 3 of pretreated solid residue in dry basis) that we used and the ethanol titre (33.4 g p l −1 ) with P. kudriavzevii SI were higher than those with S. cerevisiae KF‐7, that is a solid loading of 15% (w/w) and 21.5 g p l −1 ethanol respectively. Although the concentration of acetic acid presented in their SSF process was similar with that in our study, the concentration of furans presented in their results (furfural 0.8 g l −1 and 5‐HMF 0.2 g l −1 ) was higher than that in our process (furfural 0.19 g l −1 ).…”
Section: Resultssupporting
confidence: 87%
“…Lignocellulosic hydrolysate of rape straw was prepared by diluted sulfuric acid treatment, as described previously. 28 Main inhibitors in the hydrolysate were acetic acid, formic acid, furfural, and 5-HMF, and the concentrations were 64.45 mM, 1.06 mM, 7.29 mM, and 7.61 mM, respectively. Besides, the concentration of total phenolic compounds was 0.3 g/L.…”
Section: Methodsmentioning
confidence: 96%
“… 22 Furfural, 5-HMF, acetic acid, and formic acid concentrations were determined using a LC-10AD VP HPLC (Shimadzu, Japan) under the following conditions: temperature, 65_C; mobile phase, 0.5 mM H 2 SO 4 at a flow rate of 0.8 mL/min. 28 The concentration of the total phenolic compounds was determined using a Folin–Ciocalteu assay as described by Guo et al, 29 with minor modification. One millliter of the hydrolysate was mixed with 5 mL of distilled water, 1.5 mL of Folin–Ciocalteu reagent (Sigma–Aldrich), and 2 mL of 10% (w/v) Na 2 CO 3 .…”
Section: Methodsmentioning
confidence: 99%
“…The catalytic activity increased when the straw content in the straw/sludge mixture was increased from 50% to 80% (Figure ). The main reason might be that the carbon content in the straw is higher than that in the sludge, which provided the framework of activated carbons . Moreover, a large number of oxygen‐containing functional groups was formed which facilitate the catalysis activity .…”
Section: Resultsmentioning
confidence: 99%